Hippocampal lesions, species-typical behaviours and anxiety in mice. - Deacon, R; Rawlins, J (2005)
The hippocampus is believed to play an important role in spatial cognition and anxiety. Much of the supporting evidence is derived from rat studies. Recent reports on hippocampal lesioned mice also showed impairments in spatial function, but anxiety was not uniformly diminished. There were, however, striking impairments in several "species typical" behaviours; lesioned mice made poorer nests, and hoarded and burrowed less. In the present experiments, mice with excitotoxic hippocampal lesions were tested in a well-established anxiety paradigm, the light-dark box. As in previous anxiety tests, the results were mixed; some measures (reduced dark time) suggested lesioned mice were less anxious; others (fewer light-dark transits) suggested greater anxiety. However, lesioned mice only made fewer transits when the door was small. This suggested that the tendency to enter small holes, so characteristic of small rodents, was reduced; subsequent tests showed lesioned mice preferred to explore in an alley rather than enter its attached tunnels. Further tests of "species typical" behaviours revealed that lesioned mice spent less time digging and climbing, and made less use of cardboard shelters in their cages. This was not due to inactivity; lesions did not reduce grooming or locomotion. Finally, tests of hyponeophagia showed hippocampal lesions reduced this measure of anxiety, so long as the control baseline was sufficiently high. Overall, the results suggest that the hippocampus is important in many species-typical behaviours, potentially influencing performance in a range of behavioural tests. However, species-typical behaviours offer easy and economical ways to test for hippocampal dysfunction, for example, in genetically modified mice.